Effect of Educational Level on Oral Health in Peritoneal and Hemodialysis Patients - Gulsen Bayraktar; Idil Kurtulus; Rumeyza Kazancioglu; Isil Bayramgurler; Serdar Cintan; Canan Bural; Mine Besler; Sinan Trablus; Halim Issever; Nilgun Aysuna; Oktay Ozkan; Alaattin Yildiz (Hindawi Limited, 2009)
Background. In previous studies, the oral and dental health statuses were compared in hemodialysis (HD) and peritoneal dialysis (PD) patients without taking into account the effect of educational levels on oral health. Hence we aimed to make a comparison of these parameters based upon the subjects educational levels. Patients and Methods. 76 PD (33 males, 43 females-mean age: 44±12 years) and 100 HD (56 males, 44 females-mean age: 46±14 years) patients were included. The number of decayed, missing and filled teeth were detected, DMFT index was calculated and plaque index (PI) values were assessed. Results. Significantly higher numbers of filled teeth (P<.001) and lower PI values (P<.01) in the PD group were detected with higher educational levels, whereas no significance was detected in the HD group. Higher DMFT index values were assessed in the lower educated and high school levels in PD than HD patients (P<.05). Higher numbers of filled teeth (P<.05) were detected in the secondary school level in PD patients. This difference was even more significant in the high school level (P<.001). Conclusion. We assume that PD patients, who were found to be in a higher educational level, are more caring for their oral health as compared to HD patients.